Deletable blockchain based on threshold ring signature - Yanli REN; Danting XU; Xinpeng ZHANG; Dawu GU (Tongxin xuebao)
With the development of blockchain,huge storage space is needed to store all of blockchain data.In addition,data can’t be changed once it is packaged into the chain,and it may be possible for overdue data to take up large storage space.Firstly,a threshold ring signature scheme was improved,and then a deletable blockchain scheme based on the mechanism of proof of space (PoSpace) consensus was constructed.Most of nodes could sign and delete a block together when block data was overdue,and the overall structure of the blockchain was unchanged.Several experiments in a simulated environment were executed,and the results show that the proposed blockchain scheme has high efficiency in generating and delegating a block.Meanwhile,the deletion of a block doesn’t influence the storage and use of other blocks.